Da'wah Management of the Majelis Dakwah Islamiyah in the Rehabilitation of Drug Abuse Victims in Pekanbaru - Mahmudannisa; Maulana Andi Surya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Drug abuse refers to the non-medical use of narcotics and other addictive substances that may lead to substance dependence and adversely affect individuals' physical, psychological, social, and spiritual well-being. This study examines the da'wah management practices of the Majelis Da'wah Islamiyah (Islamic Propagation Council) in providing religious counseling and rehabilitation for victims of drug abuse in Pekanbaru, Indonesia. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings indicate that the Council systematically applies the core functions of da'wah management—planning, organizing, implementation, and evaluation—in delivering its rehabilitation programs. Religious guidance is conducted through both preventive and curative approaches, incorporating activities such as Islamic lectures, congregational prayers, dhikr (remembrance of God), Qur'anic recitation, Islamic counseling, religious study circles, and Friday sermons. These interventions contribute to positive behavioral transformation, strengthen participants' spiritual awareness, and improve their relationships with family members and the wider community. The findings underscore the potential of faith-based da'wah management as an effective complementary approach to the social and spiritual rehabilitation of individuals recovering from drug abuse